Flow Cytometry in Diagnosis of Myelomatous Pleural Effusion: A Case Report - Arora, Parul (Indian J Hematol Blood Transfus, 2015)
Plasma cell myeloma is a multifocal plasma cell neoplasm associated with increased monoclonal protein in serum and/or urine. Pleural effusions in patients with myeloma are uncommon (6 %). However, effusions due to direct infiltration of the pleura by plasma cells (myelomatous pleural effusion) are extremely rare (<1 %) and usually seen with IgA myeloma. The diagnosis of such cases requires pleural fluid cytology, electrophoresis or pleural biopsy. We present a case of myelomatous pleural effusion diagnosed using flow cytometry immunophenotyping in addition to the pleural fluid cytology. A 45 year old female was diagnosed as plasma cell myeloma (IgG kappa) in 2007. She received multiple lines of therapy during the course of her treatment including thalidomide, dexamethasone, lenalidomide, bortezomib, and doxorubicin based regimens. However, the patient had progressive extramedullary disease and developed pleural effusion in 2014. Cytological examination of the pleural fluid showed degenerative changes. Few preserved areas showed mononuclear cells including morphologically abnormal plasma cells. Immunophenotyping of these cells by flow cytometry revealed a pattern indicating neoplastic plasma cells. There was expression of CD38, CD138, and CD56, with absence of CD19, CD10 and CD45. This confirmed the diagnosis of myelomatous pleural effusion. Subsequently, the patient was offered a dexamethasone, cyclophosphamide, etoposide and cisplatin based regimen but, she declined further treatment and succumbed to her disease 3 months later. Myelomatous pleural effusion is a rare complication of plasma cell myeloma. Flow cytometry can be used as an adjunctive technique in its diagnosis particularly in cases with equivocal cytology and electrophoresis findings.